"Deutsches Requiem" by Borges. The Asceticism of the Fascist Subject - Luis Bautista (Catedral Tomada: Revista de Crítica Literaria Latinoamericana, 2020)
The critics that have analyzed Jorge Luis Borges’ “Deutsches Requiem” (1946) have usually focused on the moral inconsistencies committed by its protagonist and narrator, a Nazi officer: Otto Dietrich zur Linde. Otto explicitly states that the goal of Nazism was the destruction of Judeo-Christian values, but he is apparently unable to think outside them. All his autobiography is told through the ascetic ideal, which would make his last message incongruous. The asceticism of Otto, of the "fascist subject", is not to my view a deliberate incongruity of Borges's text. I show in this article that Otto’s deeply ascetic nature is the ultimate result of the model of subjectivity developed by western philosophy.